2005
DOI: 10.1080/10646170590915862
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Environmental Pollution Coverage in the Mainstream, African American, and Other Alternative Press

Abstract: Research has suggested that the present media merger frenzy will result in onedimensional content due to a reduced number of media outlets and pervasive crossownership. This research examined 1,180 articles about environmental pollution over 29 years from four different groups of newspapers, each with different geographic location,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The two cities where the newspaper firms are based (Crest and Die) are well represented. Many local issues attract the attention of newspapers due to their geographic proximity (Kenix 2005). Llasat et al (2007) showed that events in urban areas receive greater coverage than those in rural areas; however, the Drôme basin showed a different pattern.…”
Section: Questioning Integration At the Watershed Scalementioning
confidence: 99%
“…The two cities where the newspaper firms are based (Crest and Die) are well represented. Many local issues attract the attention of newspapers due to their geographic proximity (Kenix 2005). Llasat et al (2007) showed that events in urban areas receive greater coverage than those in rural areas; however, the Drôme basin showed a different pattern.…”
Section: Questioning Integration At the Watershed Scalementioning
confidence: 99%
“…Despite the region’s common water challenges due to water scarcity, increasing and conflicting water demands, and forces compromising water quality, there seems to be a local nuance to newspaper coverage of water. Thus, this study suggests that despite documented trends of one‐dimensional media and a loss of social responsibility to distinctive communities (Kenix ) there still remains a hybrid geography (Howe ) or local “flavor” that differentiates local newspaper coverage of water issues. Together, these seven newspapers from the core of the Intermountain West region paint a picture of some common water challenges, along with unique local experiences, and consideration of broader national and international water issues.…”
Section: Discussionmentioning
confidence: 90%
“…Previously published findings of geographic variation in news coverage surrounding environmental issues are relatively consistent with the broader research literature concerning regional news coverage. While globalizing forces such as media mergers and commercial interests create pressures for more generic coverage in newspapers (Kenix ), newspapers represent regional power dynamics in their allocation of space to news items (McGregor ). Therefore, newspapers create “hybrid geographies” reflecting “both real space and nonspatial characteristics of news consumers” (Howe , 43).…”
Section: Introductionmentioning
confidence: 99%
“…Future research is needed to thoroughly examine these issues involving audience capacity to absorb complex or written health information on various breast cancer topics appearing in different channels. One content analysis of more than 1,000 newspaper articles about environmental pollution over three decades shows that the news coverage is overwhelmingly directed to the highly educated segment of the public rather than to the broad audience (Kenix, 2005). Covello and Peters (2002) assert that many women misperceive breast cancer health risks based on media information sources, and that this contributes to a lack of taking appropriate prevention measures.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%